Job Insecurity and Achievement Motivation of Honorary Teachers - Doddy Hendro Wibowo (PSIKODIMENSIA, 2018)
Teacher is a unique job, a job that requires a high commitment beyond the desire for money. This study is for the empirical interest of the relationship between job insecurity and achievement motivation by Honorary Teacher. This study involved 95 teachers with honorary status from 34 educational institutions in kindergarten, elementary / junior high school, high school / vocational school in the suburbs of Salatiga, Central Java. Based on trials with N = 95 there is no significance of Job Insecurity and Achievement Motivation in Honorary Teachers in Salatiga, Central Java (r = 0.045; p = 0.668> 0.05; 2-tailed). This means, job insecurity does not give effect to achievement motivation by Honorary Teachers in Salatiga.